Seasonal Movement Patterns of the Bigfin Reef Squid Sepioteuthis lessoniana Predicted Using Statolith δ18O Values - Chiang, Chun-I; Chung, Ming-Tsung; Shiao, Jen-Chieh; Wang, Pei-Ling; Chan, Tin-Yam; Yamaguchi, Atsuko; Wang, Chia-Hui (Frontiers in Marine Science, 2020)
Sepioteuthis lessoniana is a widely distributed neritic squid in the Indo-Pacific Ocean. It is an important species in fisheries, but species management is difficult because of inadequate information regarding its life history. The daily growth and δ18O values from the core to the edge of statoliths of S. lessoniana collected in northern Taiwan were analyzed to predict the experienced temperature history along with ontogenetic stages. The probability of occurrence in a given area at each life stage in three seasonal groups was determined using salinity values, deduced and measured temperatures, and the known ecology of S. lessoniana. The results showed that ontogenetic variation in the statolith δ18O values in S. lessoniana reflected the seasonal temperature fluctuation observed in Taiwanese waters, which indicated the reliability of the prediction method. Complex and diverse distribution and movement patterns were observed in the three seasonal groups. The results also indicated the importance of the waters near the coast of northeastern Taiwan as a spawning ground. Based on a model prediction, the distribution of S. lessoniana is likely associated with water temperature and current. A potential migration route from the Penghu Islands to northeastern Taiwan suggests a high level of population connectivity in S. lessoniana in Taiwan. This study provides information on the spatial and vertical distribution of S. lessoniana at various ontogenetic stages, which is essential for resource management and conservation of this commercial species.